Горячий снег: роман / Юрий Бондарев - Бондарев Юрий Васильевич (Азбука-классика, 2017)
Экземпляры: Ф. 10 (20190730) / Инвентарный номер: 47140 / Цена: 130.00 / Сис.шифр: Р2 / Авт.знак: Б 81 / ГРНТИ: 17.82.30 / ББК: 84 (2Рос=Рус)6-44